The Process of Adaptation to Country by Contry Reporting (CbCR): An Evaluation on Turkey - Esra Uygun (Maliye Çalışmaları Dergisi)
BEPS Action Plan 13, “Transfer Pricing Documentation and Country-by-Country Reporting”, offers a solution to the transfer pricing problem through documentation and international information exchange. This document is based on a three-stage approach: master file, local file, and country-by-country report (CbCR). CbCR, a key component of ensuring transparency of the BEPS project, is the requirement for all major multinational enterprises above the agreed revenue threshold to submit country-by-country reports containing comprehensive details on the allocation of their global revenues, taxes paid, and the distribution of their economic activities. CbCR is shared with the tax administrations of other countries in which multinational enterprises operate, enabling the evaluation of transfer pricing risks and other risks related to the BEPS. Turkey submitted reports since 2019 within the scopeofharmonisationeffortswiththeBEPSActionPlan13minimumstandards.In addition, a necessary legal framework has recently been created. Turkey has largely complied with the action plan, except for a few differences. These differences relate to definitions, timeliness, and the leal basis for using CbCR information. In this study, Turkey’s development in its adaptation to Action Plan 13 was examined, considering OECD reports and current regulations. Although compliance has been achieved to a large extent, new regulations are needed to expand international information exchange agreements and comply with global standards.